Digital Transformation in the Financial Sector: Implications for Consumer Trust and Security - Andri Prabu; Siti Nurhaliza (International Journal of Economics, Commerce, and Management, 2024)
The financial sector is undergoing rapid digital transformation, driven by innovations in digital banking, fintech, and AI-driven solutions. This transformation has significant implications for consumer trust and data security. This paper explores the impact of these technological advancements on customer confidence in financial institutions, especially in light of recent data breaches and cybersecurity threats. By analyzing regulatory responses and cybersecurity frameworks, the study emphasizes the critical need for robust protections to build and maintain consumer trust in digital finance. Findings indicate that enhanced security measures and regulatory oversight are essential in safeguarding data and supporting the sustainable growth of digital finance.